Consensus guidelines for the management of vestibular schwannoma for lowand middle-income countries - Syed Ather Enam; Muhammad Shakir; Ahsan Ali Khan; Muniba Tahir; Kaynat Siddiqui; Muhammad Shahzad Shamim; Mohammad Hamza Bajwa; Asim Hafiz; Ahmed Gilani; Faiza Urooj; et al. (Journal of the Pakistan Medical Association, 2024)
Vestibular Schwannoma (VS), previously known as acoustic neuroma, constitutes the majority of tumours found in the cerebellopontine angle (CPA). Most guidelines for managing CPA tumours have been developed by high-income countries (HICs). However, these guidelines often fall short in addressing the unique challenges encountered in low- and middle-income countries (LMICs), such as Pakistan. In LMICs, issues related to a limited healthcare workforce, inadequate infrastructure, and constrained financial resources hinder the effective implementation of these HIC-derived guidelines. Additionally, it has been observed that VS tends to present at a larger size in LMICs compared to HICs. Given that VS is the predominant type of CPA tumour and other types are covered under separate guidelines, this article aims to provide practical, contextspecific recommendations for the screening, diagnosis, and management of Vestibular Schwannoma in LMIC settings. Our focus is to bridge the gap in care strategies and adapt them to the resource constraints and clinical realities of LMICs. Keywords: Neuroma, acoustic, cerebellopontine angle, health care, vestibular schwannoma, radiosurgery, tumours